Facile synthesis of three-dimensional MgFe2O4/graphene aerogel composites for high lithium storage performance and its application in full cell. (15th November 2019) - Luo, Lei; Chen, Zhi; Ke, Huizhen; Sha, Sha; Cai, Guangming; Li, Dawei; Yang, Hongjun; Yang, Xiaowei; Zhang, Ruquan; Li, Jianqiang; Li, Yonggui; Xu, Jie; et al.
Abstract: MgFe2 O4 /graphene aerogel (MFO/GA) composites were designed and fabricated through a combined electrospinning technique and hydrothermal-induced self-assembly strategy, in which the MFO nanofibers with high crystallinity were wrapped homogeneously and tightly. The as-synthesized MFO/GA composites formed a three-dimensional (3D) conductive network structure with large surface area, high porosity, and high conductivity, which are favorable to accommodate the volume changes of MFO during the repeated lithiation-delithiation processes, shorten the diffusion path, and promote the ions/electrons transfer. As anode material for half-cell, a high reversible capacity of 1104 mAh g −1 is obtained after 200 cycles at a current density of 0.1 A g −1 . Even at 1 A g −1, the MFO/GA delivers a stable capacity of 686 mAh g −1 over 500 cycles, exhibiting superior rate performance. When assembled with commercial LiCoO2 cathode to build a full cell system, the MFO/GA anode also can show a reversible capacity of 714 mAh g −1 after 100 cycles at 0.1 A g −1 . The excellent electrochemical performance of MFO/GA in both half and full cells indicates its potential application in practical lithium-ion batteries in the future. Graphical abstract: Unlabelled Image Highlights: MgFe2 O4 /graphene aerogel anodes have been facilely prepared by combination of electrospinning and hydrothermal. MgFe2 O4 nanofibers were wrapped in graphene aerogel to form 3D conductive network. The reversible capacity can reach 1104 mAh g −1 after 500 cycles in half-cell. The full cell exhibited a stable capacity of 714 mAh g −1 after 100 cycles.